Adaptations for nectar-feeding in the mouthparts of long-proboscid flies (Nemestrinidae: Prosoeca) - KAROLYI, FLORIAN (2012)
The insects with the longest proboscis in relation to body length are the nectar-feeding Nemestrinidae. These flies represent important pollinators of the South African flora and feature adaptations to particularly long-tubed flowers. The present study examined the morphology of the extremely long and slender mouthparts of Nemestrinidae for the first time. The heavily sclerotized tubular proboscis of flies from the genus Prosoeca is highly variable in length. It measures 20–47 mm in length and may exceed double the body length in some individuals. Proximally, the proboscis consists of the labrum–epipharynx unit, the laciniae, the hypopharynx, and the labium. The distal half is composed of the prementum of the labium, which solely forms the food tube. In adaptation to long-tubed and narrow flowers, the prementum is extremely elongated, bearing the short apical labella that appear only to be able to spread apart slightly during nectar uptake. Moving the proboscis from resting position under the body to a vertical feeding position is accomplished in particular by the movements of the laciniae, which function as a lever arm. Comparisons with the mouthparts of other flower visiting flies provide insights into adaptations to nectar-feeding from long-tubed flowers.